Microscopic life stages of Arctic kelp differ in their resilience and reproductive output in response to Arctic seasonality. Issue 4 (2nd October 2022) - Silva, Cláudio F.; Pearson, Gareth A.; Serrão, Ester A.; Bartsch, Inka; Martins, Neusa
ABSTRACT: Kelp forests are important habitats in the strongly environmentally and seasonally variable Arctic. There is a critical lack of knowledge about how seasonal conditions and climate change scenarios influence survival and reproduction of kelp early life stages. To better understand the regulation of kelp life cycle processes in this harsh environment we focused on the physiological performance and reproductive success of early life stages in Alaria esculenta and Laminaria digitata from Kongsfjorden, Spitsbergen. Gametophyte growth and survival during Arctic winter and subsequent sporophyte recruitment under spring conditions were investigated. Winter conditions (2°C, complete darkness) halted gametophyte growth and prevented the onset of gametogenesis in both species. The gametophytes of L. digitata but not A. esculenta became fertile after returning to spring conditions, suggesting that sporogenesis, sexual reproduction and recruitment in A. esculenta must occur successively during summer/autumn while in L. digitata a new generation of sporophytes could develop from over-wintering gametophytes. The effects of simulated canopy shading (offering protection against extreme irradiance stress, particularly as sea ice retreats), present-day and projected Arctic summer seawater temperatures, and nutrient levels on gametophyte survival, fertility and sporophyte recruitment success were also investigated in both species. A. esculenta gametophytes had greater survival and reproductive success than L. digitata, except under very low light (simulating dense canopy). In contrast, shading was required for reproductive success in L. digitata gametophytes. Predicted summer temperatures of 9°C reduced sexual reproduction in both species. Interactions observed between these environmental drivers probably reflect species-specific seasonal patterns of survival and reproduction. These differences between kelp species in response to abiotic factors and light levels (simulated canopy shading) suggest that climate change could alter community structure in the Arctic through effects on sexual reproduction and sporophyte recruitment success. HIGHLIGHTS Gametophytes were able to endure long periods of darkness. Parental kelp canopy is key for gametophyte survival and recruitment. Climate change may alter kelp recruitment patterns.